Cross-Cultural Validation Into Filipino of the Consumer Assessment of Health-Care Providers and Systems Surgical Care Survey (S-CAHPS) - Torres, Gian Carlo S (J Patient Exp, 2020)
Surgical experience is increasingly being recognized; however, Consumer Assessment of Health-Care Providers and Systems Surgical Care Survey (S-CAHPS), the tool for surgical experience, is available in English and Spanish only. To measure surgical experience among Filipinos, a culturally appropriate version should be validated. This study culturally adapted the S-CAHPS into Filipino. A five-step cross-cultural validation study was conducted. Language experts conducted forward translation, back translation, and panel reconciliation. Pretesting included content validation and pretesting of the Filipino S-CAHPS. Field testing involved 55 purposively selected postoperative patients who completed a 3-part survey from March to July 2018. The English S-CAHPS was reduced to 34 items to account cultural variations, yielding an item content validity index (I-CV) of 1.00. One-sample t test and Bland–Altman plots showed good linguistic equivalence. Correlation coefficients were ≥0.30, suggestive of good conceptual equivalence. Cronbach’s alpha values were 0.83 and 0.85 indicative of good reliability. The Filipino S-CAHPS showed acceptable psychometric properties. It is a valid and culturally appropriate instrument to measure surgical experience among Filipinos which can be utilized for quality improvement measures on both practice and policy levels.